Inventarisasi dan Identifikasi Objek Daya Tarik Wisata dalam Perencanaan Pariwisata Wakatobi: Inventory and Identification of Tourism Attractions in Wakatobi Tourism Planning - Ray March Syahadat (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2022)
Wakatobi's prestige has recently dimmed compared to other similar tourism areas in Indonesia. Carrying the theme of a real underwater paradise in the center of the world's coral triangle, it is sometimes slipped by local people as hell on land. The cause of this phenomenon is the lack of understanding on the power of objects, especially objects in terrestrial areas, whereas tourists who come to Wakatobi spend time not only under the sea, but also more time on land. The aims of this study were to provide information about tourist attractions in Wakatobi in terms of originality, authenticity, uniqueness, diversity, and beauty. Data and information were collected by means of document searches and interviews with key informants. The result showed that Wakatobi cannot be viewed as just one place but the four major islands that compose it. In general, natural, historical, and cultural tourism are spread throughout the islands in Wakatobi. Icons that can be highlighted as strengths of each of the four main islands include dolphin migration attraction in Wangi-Wangi, historical and cultural heritage attractions, especially the Lariangi Dance in Kaledupa, underwater beauty in Tomia, and geological landscape of the rock garden in Binongko. All tourist attractions in Wakatobi shall be connected with the strengthening of infrastructure, which currently seems to be concentrated in the capital only.